Clinico-laboratory profile and outcome of edematous severe acute malnutrition in children aged 6 months to 5 years - Suman, Rameshwar Lal; Sharma, Bharat Lal; Meena, Pradeep; Kumar, Neeraj (International Journal of Contemporary Pediatrics, 2016)
Background: Malnutrition is still rampant in India. There are so many cases of edematous malnutrition present in Rajasthan. So we planned to study the Clinico-Laboratory profile And Outcome of Edematous Severe Acute Malnutrition in children aged 6 months to 5 years. Methods: An observational hospital based prospective study was conducted at Malnutrition Treatment Center (MTC), Bal Chikitsalya, RNT Medical College, Udaipur, Rajasthan, India from July 2015 to Dec 2015. We enrolled total 50 SAM children aged 6 Months to 5 years having nutritional edema with medical complications. All the enrolled cases were hospitalized, acute complications were treated and nutritional rehabilitation by WHO feeding protocol was done. Clinical, laboratory parameters and outcome of E-SAM were analyzed. Results: A total of 50 children were studied. Mean age of children was 16.54±11.05 months, 52.0% were male and 48.0% were female children, Majority of them were under <-3SD and <-4SD z-score (48.0%) followed by <-2SD and in <-1SD z-score (32.0%). Onset of edema reduction occurs on 3.22±0.91day, complete disappearance of edema occurs in 10.02±2.80 days, mean weight fall was 0.91±0.31% per day, mean length of stay in hospital was 14.93 ±4.10 days. Mean weight gain was 14.18±5.42 gm/kg/day and case fatality rate was nil. All these outcomes except weight gain were significantly associated with grade of edema (p value <.05). Conclusions: Majority of the patients they were in WHO z-score of <-3SD and <-4SD z-score but extremes are also occurring up to <-8SD z-score Pneumonia and tuberculosis are the affected co morbidities for outcome of E-SAM children. Disappearance of edema, and length of stay are little bit longer than usual WHO guideline recommendations and they had a significant association with grade of edema. Percentage of wt. fall also had association with grade of edema.